2018
DOI: 10.4314/tjpr.v16i12.2
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> cytotoxicity of biosynthesized titanium dioxide nanoparticles in human prostate cancer cell lines

Abstract: Purpose: To establish a green method for production of titanium dioxide (TiO2) nanoparticles (NPs) using Cinnamomum tamala (C. tamala) -ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), x-ray photoelectron spectroscopy, dynamic light scattering (DLS), transmission electron microscopy (TEM), selected-area electron diffraction, and energy dispersive x-ray spectroscopy. The in vitro cytotoxicity against D145 cells was determined using a 3-(4, 5-dimethylthiazol-2-yl)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Previous literature supports our findings by suggesting that TiO 2 nanoparticles are cytotoxic to various human cell lines and doping further improves the cytotoxic status of these nanoparticles [16]. He et al [45] elucidated concentration-dependent cytotoxic activity of TiO 2 nanoparticles in human prostate cancer cell lines. Chellappa et al [46], Ahamed et al [15], Rahmani Kukia et al [47] and Koca and Duman, [48] also reported the in vitro and in vivo cytotoxicity of TiO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 88%
“…Previous literature supports our findings by suggesting that TiO 2 nanoparticles are cytotoxic to various human cell lines and doping further improves the cytotoxic status of these nanoparticles [16]. He et al [45] elucidated concentration-dependent cytotoxic activity of TiO 2 nanoparticles in human prostate cancer cell lines. Chellappa et al [46], Ahamed et al [15], Rahmani Kukia et al [47] and Koca and Duman, [48] also reported the in vitro and in vivo cytotoxicity of TiO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 88%
“…Figure 1E shows that all the samples displayed two series of peaks, which belongs to the anatase-TiO 2 structure and the face-centered-cubic Au. The peaks at 2θ of 25.3, 47.9, 53.8, and 54.7 could be ascribed to the (101), (200), (105), and (211) planes of anatase-TiO 2 37, respectively, while the left peaks were corresponding to the (111), (200), (220), and (311) faces of face-centered-cubic Au. Thus, the presence of Au and TiO 2 in the Au@TiO 2 core-shell NPs were confirmed.…”
Section: Resultsmentioning
confidence: 97%
“…NPs can acquire similar properties through the transfer of the phytochemicals on their surface during the capping process. For example, Ahmad et al (2020) have developed a mint-based method by which spherical NPs have been obtained with a size between 20 and 70 nm, probably due to the presence of alkaloids, terpenoids and phenolics in the Mentha arvensis ethanolic leaf extract (Ahmad et al, 2020 (He et al, 2017) were involved in TiO 2 NPs biosynthesis. In general, research has focused on Angiosperm plants while Plantae kingdom comprises also gymnosperms, pteridophytes (ferns), bryophytes (mosses) and macroalgae, and for other kind of NPs these organisms have given efficient results (Acharya and Sarkar, 2014;Bhor et al, 2014;Jha and Prasad, 2010;Momeni and Nabipour, 2015).…”
Section: Plant Species Involved In the Synthesis Of Tio 2 Npsmentioning
confidence: 99%
“…Broadly, NPs are formed through the action of biochemicals on metal ions provided by a precursor salt. In the case of TiO 2 NPs, the precursor can be represented by titanium tetraisopropoxide (Landage et al, 2020), metatitanic acid (Alavi and Karimi, 2018), titanium oxysulfate (Subhapriya and Gomathipriya, 2018) or bulk forms of TiO 2 (He et al, 2017). If we go further, agrowastes or organic matter waste may represent a sustainable source of biomolecules for the green synthesis of NPs (Zamani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%